Poor Dietary Diversity Is Associated With Postpartum Depression: A Cross-Sectional Study - Zhao, Jian (Current developments in nutrition, 2021)
Postpartum depression (PPD), a major maternal health concern, gives negative effects on women health, child development and family well-being. Recently, diet quality has emerged as a possible preventative measure in ameliorating PPD, however the evidence-base exploring this association is immature. The aim of this study was to investigate the association between diet diversity and depression of postpartum women. A cross-sectional study was conducted on 554 postpartum women who set up files after delivery within 2 years at 10 community health service centers in Beijing from July to September 2017. The Edinburgh Postnatal Depression Scale(EPDS) in Chinese version was used to access the status of depression. Dietary intake was determined using a semi-quantitative food frequency questionnairea (FFQ). Dietary diversity score (DDS) was calculated based on scoring to the eight-food groups with frequency according to the Chinese Dietary Guidelines (2016). DDS ranged from 0–32, and was classified into two groups: low (≤26.5) and high (>26.5). Logistic regression models were used to estimate relationships between DDS and PPD. A total of 163 women (29.4%) were depressed above the EPDS cut-off score (≥ 13 scores). Mean (±-s.d.) of DDS was 27.9 ± 3.4. 28.7% of the subjects (n = 159) had low DDS and 71.3% (n = 481) had high DDS. After statistical adjustment for age and society correlation factors, lower DDS was significantly associated with PPD ([aOR] = 1.81, 95% [CI] = 1.13 - 2.89). The present study found that low DDS, which means poor dietary diversity was associated with PPD in Chinese women after delivery within 2 years. This study was funded by grants from Chinese Academy of Medical Sciences Innovation Fund for Medical Sciences (2019-I2M-2-007).